Belief and Role of a Teacher:In Enhancing Research Thinking among the Students - Devika, S. V. (Journal of Engineering Education Transformations, 2018)
Arthur Combs says that "Perhaps the most important single cause of a person’s success or failure educationally has to do with the question of what he believes about himself." The belief of a teacher will change the nation. It begins with an overview of traditional research on teaching in general, followed by a discussion of teacher cognition under which teacher beliefs are subsumed. The general chalk and talk does not make students involve into practical applications or research activities, the belief of teacher about research should change and pedagogies to be implemented in the class room to create interest among students about how to start research from their undergraduate life. Now a days the research on teaching and learning has shifted from a unidirectional emphasis on correlates of observable teacher behaviour with student Achievement to a focus on teachers’ thinking, beliefs, planning and decision-making processes. This paper explains the change in the teacher thinking and role of a teacher in the implementation of research in the higher educational institutions and impact on the students and their involvement in the research activities.